PERAN GURU DALAM MENGEMBANGKAN KARAKTER SISWA KELUARGA BROKEN HOME DI MI KH A. THOHIR PULUNGDOWO TUMPANG - Khuriatul Maulidah; Ika Ratih Sulistiani; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The purpose of this study is to describe the character of broken home family students at MI KH A. Thohir Tumpang, implementation of character development for broken home family students at MI KH A. Thohir Tumpang, as well as obstacles and ways to solve the character development of broken home family students at MI KH A. Thohir Tumpang. This study uses a case study research method which in this study seeks to find out what phenomena are experienced by research subjects, namely the teacher's role in developing the character of broken home students. The data collection used by the researcher is observation, interviews and documentation. Data analysis in this study uses data collection, condensation, presentation, as well as drawing conclusions and verification. The validity of the data in this study used longer observations, more in-depth interviews, expert discussions with colleagues, triangulation of sources, techniques, and time. The results showed that the teacher's role in shaping the character of students from broken home families in Madrasah Ibtidaiyah has been going quite well although there are still some obstacles experienced related to the attitude of parents when they are at home, the role of influencing relationships, and there is no idolized figure.